PENURUNAN KADAR KAFEIN KOPI ARABIKA DENGAN PROSES FERMENTASI MENGGUNAKAN NOPKOR MZ-15 - Danang Kristiyanto; Broto Dhegdo Haris Pranoto; Abdullah Abdullah (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Coffee is one of the most famous drinks in the world. Many people like to drinks coffee because it has a unique flavor. Besides its flavor, coffee also has the benefit of stimulating the brain's performance as well as antioxidants. Chlorogenic acid is the predominant antioxidants contained in coffee beans in the form of esters. Chlorogenic acid is also providing the typical aroma of coffee and a parameter to determine the quality of coffee. Besides having a beneficial substance, coffee also contain caffeine which is not good for health. One of the most famous type of coffee is civet coffee (kopi luwak). This coffee is unique because in the process of this coffee should be consumed first by the civet. The issue is populations of civet who began to decreaseand the process that makes it difficult to be produced on a large scale in a short time. In the present research we tried to apply the culture of a mixture of several types of microorganisms called NOPKOR MZ-15 for processing regular coffee that resembles the civet coffee. The coffee we use in tihis research is arabica coffee. This quality is still below the civet coffee because it contains caffeine higher. Economically,arabica coffee price is still far below the civet coffee. Through a fermentation method using NOPKOR MZ-15 caffeine contained in coffee is decomposed into ester to produce better flavor. After going through the process of fermentation, caffeine levels will drop so that the economic value of coffee also increased. This process also produces acidity that not too high so that the coffee is still safe to consumsed. This research can be obtained through alternatives to improve the quality of coffee without civet.